Investigating Laboratory Biochemical Factors in Different Types of Patients With Cardiovascular Diseases - Zeinab Bandani Tarashoki; Naser Kamyari; Atefeh Zahedi; Alireza Hazbenejad; Maryam Ban; Khadijeh Kanani; Esmat Radmanesh (Disease and Diagnosis, 2023)
Background: Due to the destructive effect of cardiovascular disease on vital organs, the study of laboratory biochemical factors in the most common heart diseases is essential to accelerate the treatment of cardiovascular patients. Materials and Methods: This study was cross-sectional and analytical. By referring to the hospital information system of educational hospitals of the Abadan University of Medical Sciences, the necessary information of 565 patients with cardiovascular diseases (e.g., demographic information and laboratory diagnostic markers) from March 21, 2019, to March 19, 2020, was extracted through the hospital information system and completed checklist. Data analysis was performed using SPSS software version 22. Results: In this study, fasting blood sugar (FBS), international normalized ratio (INR), erythrocyte sedimentation rate (ESR), Serum glutamate pyruvate transaminase (SGPT), serum glutamate oxalate transaminase (SGOT), creatinine, blood urea nitrogen (BUN), total bilirubin, creatine kinase (CK)- MB, and prothrombin time (PT) were higher than normal in patients with cardiovascular diseases. SGOT was significantly different between age groups (P=0.006), and the highest value was observed in the age group over 75 years. Moreover, FBS was significantly different between the male and female groups (P=0.002). Conclusion: FBS and some diagnostic markers such as renal markers, liver, coagulation, and inflammatory markers are abnormal in patients with cardiovascular diseases.